Modified one-stage technique of laterally positioned flap with sub-epithelial connective tissue graft for the treatment of peri-implant soft tissue dehiscence in the esthetic zone: a 5-year follow-up - Almeida, Juliano Milanezi de [UNESP]; Sa, Daniela Pereira de [UNESP]; Furquim, Elisa Mara de Abreu [UNESP]; Matheus, Henrique Rinaldi [UNESP] (Wiley-Blackwell, 2023)
BackgroundThe state of art of tissue grafting allows significant improvements in the soft tissue phenotype. The importance of appropriate soft tissue phenotype around implants is supported by recent literature. The present case report aims to describe the application of a modified one-stage technique of laterally positioned flap with sub-epithelial connective tissue graft (CTG) for the treatment of peri-implant soft tissue dehiscence in the esthetic zone. Methods and ResultsA 38-year-old female presented 4 years following prosthetic restoration, with a localized soft tissue defect in height and thickness at the buccal aspect of the implant at #11, and the abutment exposed to the oral cavity. Incisions with internal and external bevels were performed in the medial and distal margins of the dehiscence, respectively, toward the alveolar mucosa. After intrasulcular incision, the area was de-epithelialized and a split thickness flap from mesial #11 to distal #14 was elevated. A tunnel was prepared at #21. CTG was stabilized mesially, within the tunnel prepared, and distally, through simple interrupted sutures. Vertical compressive sutures were performed on the CTG. The flap was laterally positioned and secured by means of suspended sutures. Healing was uneventful, increased thickness and height of the peri-implant mucosa were observed, with great esthetic outcome. The soft tissue margin was stable at the 5-year follow-up. ConclusionThe technique described in this case report showed promising results for covering exposed implant abutment in the esthetic zone, as well as for modification of the soft tissue phenotype around dental implants. Key pointsWhy is this case new information A modified one-stage technique that allows coverage of exposed metallic displays of titanium implants while modifying the soft tissue phenotype in the esthetic zone.What are the keys to successful management of this case? Meticulous incisions and internal and external bevels. Adequate elevation to allow repositioning without tension.Adequate graft size that extends through all the recipient bed; and tension-free suture.What are the primary limitations to success in this case? Presence of an implant installed in a non-satisfactory three-dimensional position.And poor hygiene and plaque accumulation postoperatively.
Keywords: autografts; connective tissue; dental implants; mouth mucosa; plastic surgery